The genomic pool of standing structural variation outnumbers single nucleotide polymorphism by threefold in the marine teleost Chrysophrys auratus. Issue 6 (20th April 2019) - Catanach, Andrew; Crowhurst, Ross; Deng, Cecilia; David, Charles; Bernatchez, Louis; Wellenreuther, Maren
Abstract: Recent studies have highlighted an important role of structural variation (SV) in ecological and evolutionary processes, but few have studied nonmodel species in the wild. As part of our long‐term research programme on the nonmodel teleost fish Australasian snapper ( Chrysophrys auratus ), we aim to build one of the first catalogues of genomic variants (SNPs and indels, and deletions, duplications and inversions) in fishes and evaluate overlap of genomic variants with regions under putative selection (Tajima's D and π ), and coding sequences (genes). For this, we analysed six males and six females from three locations in New Zealand and generated a high‐resolution genomic variation catalogue. We characterized 20, 385 SVs and found they intersected with almost a third of all annotated genes. Together with small indels, SVs account for three times more variation in the genome in terms of bases affected compared to SNPs. We found that a sizeable portion of detected SVs was in the upper and lower genomic regions of Tajima's D and π, indicating that some of these have an effect on the phenotype. Together, these results shed light on the often neglected genomic variation that is produced by SVs and highlights the need to go beyond the mere measure of SNPs when investigating evolutionary processes, such as species diversification and adaptation.